An Unusual case of flaccid Quadriplegia - Sebastian, Sajith; Roy, Jenny Susan (Journal of Medicine and Health Sciences Research, 2018)
This case describes a 47 years old Obese post menopausal lady with sudden onset flaccid quadriparesis with sparing of posterior column sensation .She has a prior history of Diabetes mellitus ,systemic hypertension ,Dyslipidemia , and hypothyroidism on regular .She was admitted for 1 day history of fever and malaise, laboratory parameters suggestive of a Possible a viral ethnology .She developed sudden onset of weakness, initially started on her Lower limb and progressing to her upper limb within few hours along with bladder involvement which appeared on the next day of hospitalisation prompt thinking of a demyelination like pattern after ruling out mechanical causes with a radiograph .In the background of a fever prompted thinking of a fast progressing demyelination like a GBS/ADEM and even started IVIG as there is always some time delay for MRI to arrive. The MRI report suggested of Thrombosis of ASA territory involving the anterior paramedian aspect of Medulla extending up to the upper cervical cord. She remained quadriplegic thereafter and 6 months later despite receiving antiplatelets, Physiotherapy and other supportive treatments. The case described here elaborates the clinical presentation and outcome of ASA thrombosis. ASA thrombosis though rare is be thought as a differential of acute onset flaccid quadriparesis in an acute setting .The clinical course and devastating nature of illness should be aware off. Its necessary to diagnose this syndrome in the earliest when patient presents with acute onset of motor weakness sparing the posterior column sensation